PENGENALAN KONSEP PANGIDER BHUANA KE DALAM PELATIHAN KARAWITAN BALI - Mariyana, I Nyoman; Desi Sentana, Gek Diah (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The realization of a work of art takes place through a process that takes place starting from the impulse felt by an artist to make his work until the work becomes a reality. The process can run easily and quickly, but it can also take a very long time, instead it can stop in the middle of the road, until the work that is forced never materializes. The process of cultivating works of art, includes three important stages that must be passed. The three stages used in the cultivation process to realize this artwork are: exploration (exploration), experimental (Improvisation) and formation (Forming) stages. In the Lontar Prakempa, a Balinese gamelan mythology which is thought to be quite old, contains ins and outs of Balinese gamelan which essentially contains tatwa (philosophy or logic), morality (ethics), longo (aesthetics) and gegebug (technique) which are in harmony with Balinese gamelan . In the lontar also explained about the concept of Pangider Bhuana as a symbol of the ruler of the universe. In the Lontar Prakempa, a Balinese gamelan mythology which is thought to be quite old, contains ins and outs of Balinese gamelan which essentially contains tatwa (philosophy or logic), morality (ethics), longo (aesthetics) and gegebug (technique) which are in harmony with Balinese gamelan . In the lontar also explained about the concept of Pangider Bhuana as a symbol of the ruler of the universe